The Performance Motivation of Cha-am Municipality Officers Phetchaburi Province - Tanaboriboon , Tissadee (International Journal of Development Administration Research, 2022)
The purpose of this research was to the performance motivation of Cha-am Municipality officers Phetchaburi Province. This is a quantitative method. Samples group classified by gender, age, educational level and average monthly income with the level of motivation in the performance of Cha-am Municipality Officers Phetchaburi Province. The statistics used in the data analysis were frequency, percentage, mean, standard deviation and the variance t-test, F-test. The result showed that: performance motivation of Cha-am Municipality officers Phetchaburi Province according to the motivating factor overall, it is at a high level. When considering each aspect, it was found that the nature of the work performed with the highest average, followed by recognition and respect the success of a person’s work in terms of progress in work and responsibility with the lowest mean, respectively, according to the tuning factor overall, it is at a high level when considering each aspect working environment with the highest average, followed by interpersonal relations in the department